Using Intradermal Rabies Vaccine to Boost Immunity in People with Low Rabies Antibody Levels - Brown, David (SAGE-Hindawi Access to Research, 2011)
Intradermal rabies vaccine is recommended by the World Health Organisation, but not all countries, including England, follow this recommendation. A group of 12 adults in England previously given pre-exposure intradermal rabies vaccine were considered to be non-immune to rabies because their rabies antibody titres were known to be less than 0.5 IU/mL. A cohort study examined the immunizing effect of increasing the participants' cumulative dose of intradermal rabies to 2.0 IU. All patients subsequently demonstrated rabies antibody levels >0.5 IU·mL supporting evidence of adequate sero-conversion. No adverse effects of intradermal rabies vaccine boosting were noted. Within the limits of a small study the findings support the hypothesis that adequate levels of rabies antibody can be achieved by a schedule of intradermal injections delivered on at least three occasions with a cumulative rabies vaccine dose of 2.0 IU.